TECHNOLOGY-BASED ASSESMENT OF REGIONAL COMPETITIVENESS FOR AGROINDUSTRY DEVELOPMENT USING FUZZY APPROACH - Suci Wulandari dan Marimin (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT Regional development is undertaken by governments with the aim of improving the prosperity of people.  It is closely related to phenomenon of globalization and regional autonomy. Strategic objective attempts to increase regional competitiveness significantly. Commodity based development is a concept of development which is used in most regions in Indonesia, however the performance of agroindustry has not been optimal yet. This is part of problems associated with technology management aspect. Therefore, it is necessary to develop a measurement model to determine the status of technology as indicator of region competitiveness, construct the model mapping technology status of a region and create a model of the selection policy for the development of agroindustry. The process consists of analysis of several aspect, those are technological component, technological ability, technological climate and technological infrastructure. Analyses were done using the system approaches with fuzzy logic and artificial neural network covering: Fuzzy Inference System, Adaptive Neuro-Fuzzy Inference System (ANFIS) and Fuzzy–Analytical Hierarchy Process (Fuzzy–AHP).  Through this phase, regional competitiveness can be assessed and improvement policy as consequences on the technologycal achievement can be developed. Keywords: competitiveness, technology, agroindustry, fuzzy approach, artificial neural network.